If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(5n-2)-3n+7=154
We move all terms to the left:
-2(5n-2)-3n+7-(154)=0
We add all the numbers together, and all the variables
-3n-2(5n-2)-147=0
We multiply parentheses
-3n-10n+4-147=0
We add all the numbers together, and all the variables
-13n-143=0
We move all terms containing n to the left, all other terms to the right
-13n=143
n=143/-13
n=-11
| T=2s+16.21 | | 3(x+8)=9(x+3 | | 7x+12=-7+3x | | | | |2x+3|-9=12 | | 1 x+6=16 | | 33=-8v+3(v+6) | | 5x+13=9x+5 | | -9p-8=-8p | | 3v=2v+36 | | | | 6x-1=3x-40 | | 4(1-5a)=-6(7a-8) | | | | | | | | | | | | | | 15x-42=143 | | 7(9+n)=84 | | 5+1/3x-9=-2 | | t=-4t^2+16t+48 | | 2x-5(x-3)=9x-10) | | -5x+8=−5x+8=-4x+9−4x+9 | | 15-42x=143 | | 3x-3=9-1x | | 4y+2(y-7)=130 | | (x)/(-5)=-8 | | 59=x-8 | | X+(2y-9)=24 | | F(1/3)=8-3x |